Fabrication of 3D printed patient-derived anthropomorphic breast phantoms for mammography and digital breast tomosynthesis: Imaging assessment with clinical X-ray spectra. (June 2022) - Varallo, Antonio; Sarno, Antonio; Castriconi, Roberta; Mazzilli, Aldo; Loria, Alessandro; del Vecchio, Antonella; Orientale, Antonio; Pilotti, Immacolata A.M.; D'Andria, Pasquale; Bliznakova, Kristina; Ricciardi, Roberta; Mettivier, Giovanni; et al.
Highlights: Fused deposition modelling 3D printing technology to manufacture anthropomorphic breast phantoms. Phantoms for digital mammography and breast tomosynthesis derived from patient breast CT. PLA, ABS and PET thermoplastic filaments as substitutes of breast tissues. Evaluation of the anatomical noise in DM, DBT and CT images of the 3D printed phantoms. Promising application for quality assurance, image quality and dosimetry assessments. Abstract: Purpose: To design, fabricate and characterize 3D printed, anatomically realistic, compressed breast phantoms for digital mammography (DM) and digital breast tomosynthesis (DBT) x-ray imaging. Materials: We realized 3D printed phantoms simulating healthy breasts, via fused deposition modeling (FDM), with a layer resolution of 0.1 mm and 100% infill density, using a dual extruder printer. The digital models were derived from a public dataset of segmented clinical breast computed tomography scans. Three physical phantoms were printed in polyethylene terephthalate (PET), acrylonitrile–butadiene–styrene (ABS), or in polylactic-acid (PLA) materials, using ABS as a substitute for adipose tissue, and PLA or PET filaments for replicating glandular and skin tissues. 3D printed phantoms were imaged at three clinical centers with DM and DBT scanners, using typical spectra. Anatomical noise of the manufactured phantoms was evaluated via the estimates of the β parameter both in DM images and in images acquired via a clinical computed tomography (CT) scanner. Results: DM and DBT phantom images showed an inner texture qualitatively similar to the images of a clinical DM or DBT exam, suitably reproducing the glandular structure of their computational phantoms. β parameters evaluated in DM images of the manufactured phantoms ranged between 2.84 and 3.79; a lower β was calculated from the CT scan. Conclusions: FDM 3D printed compressed breast phantoms have been fabricated using ABS, PLA and PET filaments. DM and DBT images with clinical x-ray spectra showed realistic textures. These phantoms appear promising for clinical applications in quality assurance, image quality and dosimetry assessments.